Microscopic characterization and formation mechanisms of deep-water sandy-debris-flow and turbidity-current sandstones in a lacustrine basin: a case study in the Yanchang Formation of the Ordos Basin, China - Jian-Bo Liao (KeAi Communications Co., Ltd., 2018)
Abstract Deep-water deposition is a current issue in sedimentological research. Sandy-debris-flow sandstones and turbidity-current sandstones are the main types of sandstone that are the focus of considerable disputes in this research. Previous studies mainly focused on description of the macroscopic sedimentary structure and theoretical derivation of the formation mechanisms. The microscopic petrological characteristics, reservoir properties, and formation mechanisms of deep-water sandy-debris-flow and turbidity-current sandstones have been studied in the Yanchang Formation of the Ordos Basin, China, by means of field outcrop surveys, thin-section identification, geochemical element analysis, and porosity and permeability measurements under overburden pressure. The content of detrital grains in the sandy-debris-flow sandstones is high, whereas the contents of mica sheets and matrix are low. The fine-grained matrix is distributed unevenly within the pores. A considerable number of residual intergranular pores are preserved in the middle of single sand bodies, resulting in relatively better reservoir properties. The total number of detrital grains in the turbidite sandstone is low, while it contains abundant mica sheets and matrix. The mica sheets and fine-grained matrix are distributed evenly within the pores, resulting in serious damage to pores and poor reservoir properties. The sandy-debris-flow sandstones in the center of the lake basin form a high-quality reservoir; thus, this area is suitable for oil and gas exploration.